A national study through a 'Farm‐to‐fork' Approach to determine Salmonella dissemination along with the Lebanese poultry production chain. (17th March 2022) - El Hage, Rima; El Rayess, Youssef; Bonifait, Laetitia; El Hafi, Bassam; Baugé, Louise; Viscogliosi, Eric; Hamze, Mounzer; Mathieu, Florence; Matar, Ghassan M.; Chemaly, Marianne
Abstract: This cross‐sectional study was conducted to determine the prevalence of Salmonella at different stages of the broiler production chain and layer flocks in addition to their antibiotic resistance profile and molecular patterns. Over a period of 3 years, different sample matrices were collected from Lebanese farms, slaughterhouses and retail markets. Out of 672 Salmonella serotyped, 514 were analysed for antimicrobial resistance and 214 for clonality using Pulsed‐field gel electrophoresis (PFGE). The results highlighted an important prevalence of Salmonella, 30% in farms, 35.8% in slaughterhouses and 22.4% at retail level. A large diversity of serotypes was identified with predominance among Salmonella Infantis (32.9%), Salmonella Enteritidis (28.4%) and Salmonella Kentucky (21.4%). High resistance to nalidixic acid was revealed in all the isolates. The most prominent resistance was exhibited in S . Kentucky and S . Infantis. The latter was resistant to tetracycline (99%), streptomycin (88.2%) and remarkable multi‐drug resistance (MDR) (89.7%). All S . Kentucky isolates were resistant to ciprofloxacin, MDR (62.4%) and 6% were resistant to extended‐spectrum cephalosporin (ESCs). One persistent clone of S . Enteritidis was found common between poultry and humans. Similar genomic profiles were detected between farms, slaughterhouses and retail suggesting the dissemination of identical clones throughout the food chain possibly due to weak barriers preventing such transmission.